YWCA Building, Panama-Pacific International Exposition, main stairway and other interior details, 1914 - Julia Morgan::::::::: (1914)
Note on the drawing reads: 'Exterior design is furnished by the P.P.I.E Co. The work of Edward F. Champney and is same as for press building.'